2003
DOI: 10.1055/s-2003-42614
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Pancreatitis Following Endoscopic Retrograde Cholangiopancreatography: A Meta-Analysis

Abstract: This meta-analysis provides a clear basis for planning pharmacological studies or studies of new endoscopic techniques in patients at high risk of developing post-ERCP pancreatitis. Knowing which patients are most at risk may also make it easier to decide who should be considered unsuitable for same-day discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(89 citation statements)
references
References 14 publications
(22 reference statements)
5
70
2
1
Order By: Relevance
“…Technique-related factors have also been reported, including repeated and traumatic papillary cannulation, pancreatic sphincterotomy, biliary dilation without prior sphincterotomy, biliary sphincterotomy and precut (6,8). Protective factors include advanced age, malignant stricture and chronic pancreatitis (5).…”
Section: Endoscopic Retrograde Cholangiopancreatography (Ercp) Is a Dmentioning
confidence: 99%
“…Technique-related factors have also been reported, including repeated and traumatic papillary cannulation, pancreatic sphincterotomy, biliary dilation without prior sphincterotomy, biliary sphincterotomy and precut (6,8). Protective factors include advanced age, malignant stricture and chronic pancreatitis (5).…”
Section: Endoscopic Retrograde Cholangiopancreatography (Ercp) Is a Dmentioning
confidence: 99%
“…Results are mean ± SEM (n = 6 for each treatment) and are expressed as percentage over basal (set at 100%). Results of statistical analysis are shown as * P \ 0.05 and ** P \ 0.01 with respect to control group and # P \ 0.05 with respect to saline group during ERCP [45]. In this sense, it has been recently demonstrated that a technique that facilitates cannulation of the common bile duct prevents development of post-ERCP-AP [47].…”
Section: Discussionmentioning
confidence: 95%
“…Although the exact cause of pancreatic damage after ERCP is unknown, many studies have demonstrated that AP is a major and potentially serious complication of ERCP occurring in 1-10% of patients [42][43][44]. It has been described that pancreatic duct manipulation during ERCP could lead to injury and pancreatic juice flow obstruction [45]. Moreover, hydrostatic injury, which may occur as a result of contrast overinjection, could be a cause of pancreatitis after diagnostic ERCP [46].…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies and prospective randomized trail have failed to demonstrate the benefit of PBD on postoperative outcomes after pancreaticoduodenectomy in jaundiced patients with pancreatic head cancer [3][4][5][6][13][14][15][16][17][18][19][20]. However some meta-analysis and reviews have shown that this strategy was associated with higher rate of postoperative complications [12,13,[19][20][21][22][23].…”
Section: Discusionmentioning
confidence: 99%